2009
DOI: 10.1086/597303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofPlasmodium vivaxGenotyping Markers for Molecular Monitoring in Clinical Trials

Abstract: Even for the most diverse markers, the highest allelic frequencies reached 6% (MS16) or 13% (Pv3.27). To reduce the theoretical probability of superinfection with parasites that have the same haplotype as that detected at baseline, we propose to combine at least 2 markers for genotyping individual P. vivax infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
131
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 32 publications
2
131
0
5
Order By: Relevance
“…MS16 and msp1F3 were selected to genotype P. vivax isolates in the present study, as it has been shown previously that diversity of the two markers is sufficiently high to enable high-resolution differentiation between genetically distinct strains. 13,14 The MS16 marker is highly diverse and lacking in dominant alleles. Less diverse than MS16, the coding sequence of the msp1F3 marker is more complex than a microsatellite; therefore, artifacts introduced by slippage of the polymerase chain reaction (PCR) polymerase are less likely to occur.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…MS16 and msp1F3 were selected to genotype P. vivax isolates in the present study, as it has been shown previously that diversity of the two markers is sufficiently high to enable high-resolution differentiation between genetically distinct strains. 13,14 The MS16 marker is highly diverse and lacking in dominant alleles. Less diverse than MS16, the coding sequence of the msp1F3 marker is more complex than a microsatellite; therefore, artifacts introduced by slippage of the polymerase chain reaction (PCR) polymerase are less likely to occur.…”
Section: Methodsmentioning
confidence: 99%
“…14 Genotyping was performed as previously described, 14 with the following alterations: a multiplex first-round PCR was performed using the HotMaster Taq DNA Polymerase Kit (5 Prime, Murarrie, Queensland, Australia) and the published MS16 and msp1F3 primer sequences of Koepfli and others. 13 The primary PCR mastermix, in a final volume of 20 μL, consisted of 1 μL WGA template DNA, 2 μL 10 + HotMaster Taq buffer with Mg 2+ , 0.25 μM each primer (Geneworks, Hindmarsh, South Australia, Australia), 0.2 mM deoxynucleotide triphosphates (dNTPs) (Roche, Castle Hill, New South Wales, Australia), and 1 U HotMaster Taq DNA polymerase (5 Prime). Thermocycling was performed under the following conditions: denaturation at 94 C for 2 minutes; 30 cycles of denaturation at 94 C for 30 seconds, primer annealing at 56 C for 30 seconds, and primer extension at 65 C for 1 minute; final extension at 65 C for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of methodologies have been developed for P. vivax with as few as three polymorphic markers proving to be sufficient to discriminate homologous from heterologous infections. [73][74][75][76] However, recurrence of P. vivax genetically identical to the pretreatment isolate can occur from either a true recrudescence of the initial infection or a relapse from hypnozoites generated from the prior blood-stage infection 74,77 ; unsurprisingly molecular methods are unable to distinguish between these alternatives. Relapses are also commonly genetically heterologous.…”
mentioning
confidence: 99%